Non-pharmaceutical interventions for people living with HIV with cognitive impairment: A scoping review. - Lucinda Stuart; Kate Alford; Jamie H Vera (PLoS ONE)
Background Cognitive impairment (CI) in HIV is often of multifactorial causation, and remains a prominent issue in the age of effective combination antiretroviral therapy (cART), affecting approximately 14% of people living with HIV. Despite the 2018 BHIVA directive stating the importance of commencing rehabilitation strategies in people living with HIV with CI, no types of cognitive rehabilitations or other non-pharmaceutical interventions are specifically recommended. This scoping review aimed to describe the types of and evidence relating to the non-pharmaceutical interventions which have been examined in people living with HIV with CI. Methods Studies were identified from five electronic databases. Criteria for study inclusion were studies describing a non-pharmaceutical intervention published after 1st January 2000 in English, in a population of adults living with HIV with CI detected at baseline, without significant psychiatric or substance-misuse co-morbidity. Results Fourteen studies met the criteria for inclusion, with the Frascati criteria most commonly used to define CI within participant populations. The median intervention length was 12 weeks (IQR = 6.5). Nine studies investigated interventions with some component of computerised cognitive training (CCT); other interventions included diet, exercise and goal management training. Studies most commonly examined neurocognitive outcomes, but also considered other outcomes including quality of life, depressive symptomatology, intervention acceptability and cART adherence. Eight studies observed improvement in cognition with CCT, with effects often maintained for several weeks post-intervention, however, results were not always statistically significant. Self-reported cognitive improvement and intervention acceptability was high amongst participants completing CCT. Conclusions There was heterogeneity across studies not only in intervention type, but in diagnostic tools used, the chosen outcome measures and cognitive batteries, making comparison difficult. Findings, however, indicate that CCT interventions may produce benefits in cognition and are acceptable to patients. Further research is required in larger samples, alongside identifying specific intervention components that improve outcomes.